Universal Banks and Corporate Control: Evidence from the Global Syndicated Loan Market - Ferreira, Miguel A.; Matos, Pedro (Review of Financial Studies, 2012)
We investigate the effects of bank control over borrower firms whether by representation on boards of directors or by the holding of shares through bank asset management divisions. Using a large sample of syndicated loans, we find that banks are more likely to act as lead arrangers in loans when they exert some control over the borrower firm. Bank-firm governance links are associated with higher loan spreads during the 2003–2006 credit boom but lower spreads during the 2007–2008 financial crisis. Additionally, these links mitigate credit rationing effects during the crisis. The results are robust to several methods to correct for the endogeneity of the bank-firm governance link. Our evidence, consistent with intertemporal smoothing of loan rates, suggests that there are costs and benefits from banks' involvement in firm governance.